تطبيق حوكمة الشركات في بيئة الأعمال الدولية وتحديات تطبيقها في الجزائر - عمامرة, ياسمينة (Université de M'sila, 2017)
I've enjoyed the subject of corporate governance critical for institutions of international business and development programs, due to the recent series of financial crises that have touched the economies of certain regions of the world in the second half of the nineties, and some breakdowns experienced by major international companies, where he was in this context to make international efforts in order to establish and apply the Principles of Corporate governance by the legal and economic environment of each country. The application of corporate governance has become an international trend, since Algeria is not in isolation from the world's desire for increasing global economic integration, like other developing countries, it has made efforts to build an institutional framework for Hokh companies where she worked on improving the investment climate and seeking to opening its economy, as well as the issuance of the Charter of good governance
Keywords: corporate governance, the reality of governance in Algeria, challenges and obstacles to governance.